2022
DOI: 10.3390/pharmaceutics14061198
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic Gas Vesicles from Halobacteria NRC-1: A Potential Ultrasound Contrast Agent for Tumor Imaging

Abstract: Ultrasound contrast agents are valuable for diagnostic imaging and drug delivery. Generally, chemically synthesized microbubbles (MBs) are micro-sized particles. Particle size is a limiting factor for the diagnosis and treatment of many extravascular diseases. Recently, gas vesicles (GVs) from some marine bacteria and archaea have been reported as novel nanoscale contrast agents, showing great potential for biomedical applications. However, most of the GVs reported in the literature show poor contrast imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Compared to conventional ultrasonic contrast agents, nanoscale GVs extracted from Halobacterium NRC-1 can perfuse tumor ischemic regions and generate contrast signals due to their small particle size ( Wei et al, 2022 ). However, similar to conventional nanoparticles, most of GVs after tail vein injection were usually uptake by liver macrophages, resulting in a weak signal in the tumor ( Kreuter, 1996 ; Le Floc’h et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to conventional ultrasonic contrast agents, nanoscale GVs extracted from Halobacterium NRC-1 can perfuse tumor ischemic regions and generate contrast signals due to their small particle size ( Wei et al, 2022 ). However, similar to conventional nanoparticles, most of GVs after tail vein injection were usually uptake by liver macrophages, resulting in a weak signal in the tumor ( Kreuter, 1996 ; Le Floc’h et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrophobic GvpA forms the spindle-shaped skeleton, and the hydrophilic GvpC is arranged in the outer structure of the protein shells ( Distribution, 2012 ; Hill and Salmond, 2020 ; Volkner et al, 2020 ). Our previous studies demonstrated GVs from Halobacterium NRC-1 bacteria have about 200 nm particle size and exhibited excellent contrast imaging performance by using of clinical diagnostic ultrasound equipment at the optimized parameters ( Wei et al, 2022 ). However, owing to the shells composed of proteins, GVs are easily removed by macrophages of the reticuloendothelial system (RES) and probably bring with some immunogenicity or side effects, limiting their use in the future clinical practice ( Ling et al, 2020 ; Yan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Preparation and Characterization of E-cad-GVs and N-cad-GVs: GVs were isolated and purified from Halobacterium Salinarum NRC-1 as previously described. [24] Briefly, the bacteria were cultured for 2 weeks in a shaker at 37 °C at 220 rpm, then transferred into a separatory funnel to allow the bacteria with GVs to float to the top of the medium. The floated bacteria were collected and lysed by the hypotonic shock method.…”
Section: Methodsmentioning
confidence: 99%
“…Lipid MBs were fabricated according to the previous study. [ 24 ] The MBs used in this work were ≈1‐5 µm in particle size. The ultrasound contrast images were obtained after 60 s by using an ultrasound diagnostic system (Resona 7, Mindray, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation